An Analysis of Silicon Waveguide Phase Modulation Efficiency based on Carrier Depletion Effect - Haroon, Hazura; Hanim, Abdul Razak; Mardiana, Bidin; Menon, P.S (2010)
This paper highlights the study of carrier depletion effect on silicon waveguide with p-i-n diode and NPN structure. The device performance is predicted by using 2D Silvaco CAD software under different applied voltages. Device performances in terms of modulation efficiency will be discussed.